Developing hierarchical CdS/NiO hollow heterogeneous architectures for boosting photocatalytic hydrogen generation - Deng, Chonghai; Ye, Fan; Wang, Tao; Ling, Xiaohui; Peng, Lulu; Yu, Hong; Ding, Kangzhe; Hu, Hanmei; Dong, Qiang; Le, Huirong; Han, Yongsheng (Nano research, 2022)
The hierarchical binary CdS/NiO hollow heterogeneous architectures (HHAs) with p-n heterojunction are constructed by a facile microwave-assisted wet chemical process for high-efficient photocatalytic hydrogen evolution reaction (HER) from water. The asdesigned CdS/NiO HHAs are composed of hexagonal n-type CdS nanoparticles with a size in the range of 20–40 nm attaching to cubic p-type NiO hollow microspheres (HMSs) which are aggregates of porous nanoplates with a thickness of about 20 nm. The photocatalytic water splitting over CdS/NiO HHAs is significantly increased under simulated solar irradiation, among which the most active sample of CdS/NiO-3 (the mass ratio of CdS to NiO is 1:3) exhibits the fastest photocatalytic HER rate of 1.77 mmol·g −1 ·h −1 , being 16.2 times than that of pure CdS. The boosted photocatalytic HER could be attributed to the synergistic effect on the proportional p-n heterojunction with special hierarchical hollow and porous morphology, an enhancement of visible light absorption, and an improvement of photoinduced charge separation as well as the photo-stability given by the composite heterojunction. This work shows a viable strategy to design the heterojunction with special morphology for the efficient hydrogen generation by water splitting utilizing solar energy.